PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIK SISWA SMP SANTO PETRUS MEDAN - Sionita Surbakti; Frida Marta Simorangkir; Israil Sitepu (CV. ALIM'SPUBLISHING, 2024)
This research aims to find out whether the application of the problem based learning model can improve students' mathematical problem solving abilities in class VII of St. Peter's Middle School, Medan. This research method uses Classroom Action Research (PTK). The research procedure is cyclical. Each cycle consists of 4 stages, namely: planning, implementing actions, observing and reflecting. Data collection techniques through observation and tests. This data collection uses several instruments in the form of student observation sheets. Meanwhile, to determine students' mathematical problem solving abilities, tests are used. The results of the research show that the use of the Problem Based Learning learning model can improve students' mathematical problem solving abilities in mathematics lessons on algebra material. From the average value of prerequisite abilities, namely 55.56, the average value of students' mathematical problem solving abilities in cycle I is 72.55 and the average value of students' mathematical problem solving abilities in cycle II is 76.39 and the activity value of students in cycle I is 62%, and cycle II, namely 85%.